Transarterial chemoembolization combined with molecularly targeted agents plus immune checkpoint inhibitors for unresectable hepatocellular carcinoma: a retrospective cohort study - Jiang, Nan; Zhong, Binyan; Huang, Jintao; Li, Wanci; Zhang, Shuai; Zhu, Xiaoli; Ni, Caifang; Shen, Jian (Frontiers in Immunology, 2023)
Purpose To retrospectively evaluate and compare treatment effectiveness and safety between transarterial chemoembolization (TACE) combined with molecularly targeted agents plus immune checkpoint inhibitors (TACE+T+I) and TACE combined with molecularly targeted agents (TACE+T) for unresectable hepatocellular carcinoma (uHCC). Methods We retrospectively analyzed the data of patients with unresectable HCC from January 2018 to June 2022. The patients were screened based on the inclusion criteria and were divided into the triple combination group (TACE+T+I) and the double combination group (TACE+T). The primary outcomes were overall survival (OS), progression-free survival (PFS), and adverse events (AEs). The secondary outcomes were objective response rate (ORR) and disease control rate (DCR). Risk factors associated with PFS and OS were determined by Cox regression analysis. Results A total of 87 patients were enrolled in this study, including 42 patients in the TACE+T+I group and 45 patients in the TACE+T group. Over a median follow-up of 29.00 and 26.70 months, patients who received TACE+T+I therapy achieved a significantly longer median OS (24.00 vs. 21.40 months, p = 0.007) and median PFS (9.70 vs. 7.00 months, p = 0.017); no grade 4 AEs or treatment-related death occurred in the two groups. Grade 3 AEs attributed to systemic agents in the two groups showed no significant difference (19.0% vs. 15.6%, p = 0.667). Patients in the TACE+T+I group demonstrated better tumor response when compared with patients in the TACE+T group, with an ORR of 52.4% vs. 17.8% (p = 0.001). No significant difference was observed in DCR between the two groups (83.3% vs. 77.8%, p = 0.514). Cox regression analysis showed that only the treatment method was an independent factor of OS, and both age and treatment method were independent factors related to PFS. Conclusion Compared with TACE plus molecularly targeted agents (TACE+T), the triple therapy (TACE+T+I) could improve survival and tumor response in unresectable HCC with manageable toxicities.